Evaluation of care and clinical outcomes after the implementation of an electronic medical record system for type 1 diabetes management in Rwanda - Nathalie Bille; Dirk Lund Christensen; Knut Borch-Johnsen; Crispin Gishoma; Stine Byberg (Global Health Action)
Background Electronic medical record (EMR) systems are increasingly used to improve disease management. However, the impact on data quality, quality of care and clinical outcomes for type 1 diabetes (T1D) in sub-Saharan Africa (SSA) has not yet been explored. Objective The aim was to evaluate the effect of implementing an EMR system on the quality of care and clinical outcomes for T1D individuals in Rwanda. Methods The Rwanda Diabetes Association collected data during quarterly district hospital visits. We evaluated the effect of a newly developed and implemented EMR system by assessing differences in clinical attendance and outcomes 2 years before (pre-EMR: February 2020-February 2022) and after (post-EMR: February 2022–February 2024) the deployment of the EMR system. Results We found an increase in the number of individuals examined and the number of consultations conducted post-EMR. There was an increase in data completeness on all parameters; however, we also found that more people did not monitor their blood glucose post-EMR. We found a significant increase in clinical attendance, and a reduction in median HbA1c levels from 81.4 mmol/mol pre-EMR to 63.9 mmol/mol post-EMR (p < 0.001). Conclusion Several quality and clinical indicators improved after the integration of the EMR system in T1D management. To the best of our knowledge, this is the first study evaluating the impact of using an EMR system on the quality of care and clinical outcomes for T1D individuals in an SSA context. The long-term effect and implications are yet to be explored.